Research on Small Square PCB Rogowski Coil Measuring Transient Current in the Power Electronics Devices - Chaoqun Jiao; Juan Zhang; Zhibin Zhao; Zuoming Zhang; Yuanliang Fan (Sensors, 2019)
With the development of China’s electric power, power electronics devices such as insulated-gate bipolar transistors (IGBTs) have been widely used in the field of high voltages and large currents. However, the currents in these power electronic devices are transient. For example, the uneven currents and internal chip currents overshoot, which may occur when turning on and off, and could have a great impact on the device. In order to study the reliability of these power electronics devices, this paper proposes a miniature printed circuit board (PCB) Rogowski coil that measures the current of these power electronics devices without changing their internal structures, which provides a reference for the subsequent reliability of their designs.